Emancipatory agroecologies: social and political principles - Giraldo, Omar Felipe; Rosset, Peter Michael [UNESP] (Taylor & Francis, 2022)
We examine how the policies of governments and the projects of international agencies and many NGOs strip agroecology of its emancipatory potential. Adhering to the conventional logic of development, they reinforce or create dependencies, individualize communities, convert use values into exchange values, incorporate peoples into hierarchical structures of domination, promote the belief that peoples must be saved from poverty through the intervention of a benefactor, and teach to act based on capitalist economic rationality. Emancipatory agroecologies, on the other hand, are radically transformative processes which we summarize in seven principles.
Keywords: Agroecology; autonomy; cooptation; critique of development; social movements